Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1016/j.ijbiomac.2011.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Galactomannan thin films as supports for the immobilization of Concanavalin A and/or dengue viruses

Abstract: The immobilization of the glucose/mannose-binding lectin from Concanavalia ensiformis seeds (ConA) onto a monolayer made of a galactomannan extracted from Leucaena leucocephala seeds (GML), which was adsorbed onto - amino-terminated surfaces, was investigated by means of ellipsometry and atomic force microscopy. The mean thickness of GML monolayer, which polysaccharide consists of linear 1→4-linked β-D-mannopyranosil units partially substituted at C-6 by α-D-galactopyranosyl units, amounted to (1.5±0.2) nm. Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 46 publications
0
4
0
1
Order By: Relevance
“…17,18 Another promising application of galactomannans is their adsorption on solid substrates for immobilization of biomolecules, which can allow the development of biosensors. 19,20 Hyaluronic acid (HA) is a polysaccharide with widespread medical applications. As a component of an extracellular matrix, it can be used in ophthalmic surgeries, 21 tissue engineering 22 and as a temporary substitute for skin in burn therapy.…”
Section: Introductionmentioning
confidence: 99%
“…17,18 Another promising application of galactomannans is their adsorption on solid substrates for immobilization of biomolecules, which can allow the development of biosensors. 19,20 Hyaluronic acid (HA) is a polysaccharide with widespread medical applications. As a component of an extracellular matrix, it can be used in ophthalmic surgeries, 21 tissue engineering 22 and as a temporary substitute for skin in burn therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Con A was added at a concentration of 1 mg mL −1 in an aqueous 20 mM MOPS buffer of pH 5.5 containing 10 mM CaCl 2 and 10 mM MnCl 2 . The Ca 2+ and Mn 2+ ions play the role of co-factors [38] required to activate the protein for glucose binding. The MOPS buffer containing Con A was further diluted 10-fold in 50 mM Boric acid to a final concentration of 0.1 mg mL −1 protein.…”
Section: Con a Immobilisationmentioning
confidence: 99%
“…A potential explanation for the decay on G and G moduli for our immobilizing gel matrix comes from Valenga et al [13] study on the immobilization of the lectin extracted from Concanavalia ensiformis seeds, also known as ConA, onto a monolayer made of a galactomannan extracted from Leucaena leucocephala seeds. They suggested that because the galactomannan backbone is ␤-dmannose (1 → 4) linkage and some units at the C-6 position carries ␣-d-galactose units, the recognition of ConA might be for OH groups at the C-3 and C-6 position for the mannose units not substituted.…”
Section: Stress-strain Testmentioning
confidence: 99%
“…Many studies have reported the potential use of galactomannans as thickeners [5], part of mixed systems such as hydrogels [6], emulsion stabilizers in the preparation of films [7] and edible films themselves with enhanced barrier as well as mechanical properties that extend and improve food shelf-life [8,9]. It is also important to highlight the application of galactomannans in the cosmetic industry [10] and as matrix for immobilization of certain biomolecules [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%